2006
DOI: 10.3201/eid1211.060223
|View full text |Cite
|
Sign up to set email alerts
|

Anatidae Migration in the Western Palearctic and Spread of Highly Pathogenic Avian Influenza H5N1 Virus

Abstract: Anatids may have spread the virus along their autumn migration routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
182
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(204 citation statements)
references
References 26 publications
10
182
0
8
Order By: Relevance
“…The implication of this is that low temperatures and frost conditions influenced the pattern of introduction, spread, and persistence of the H5N1 virus. This is commensurate with the speculations of other authors (Gauthier-Clerc et al, 2007;Gilbert et al, 2006;Kilpatrick et al, 2006) that the severe cold wave in Eastern Europe, which started in January 2006, might have pushed many wintering bird species away from their usual wintering grounds.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The implication of this is that low temperatures and frost conditions influenced the pattern of introduction, spread, and persistence of the H5N1 virus. This is commensurate with the speculations of other authors (Gauthier-Clerc et al, 2007;Gilbert et al, 2006;Kilpatrick et al, 2006) that the severe cold wave in Eastern Europe, which started in January 2006, might have pushed many wintering bird species away from their usual wintering grounds.…”
Section: Discussionsupporting
confidence: 70%
“…Conversely, the global pattern of H5N1 is generally consistent with the major bird migration routes (Kilpatrick et al, 2006;Si et al, 2009), and H5N1 virus spread has been found to broadly match bird migration in the Western Paleartic (Gilbert et al, 2006). Experimental infection of swans and geese has revealed that these birds may shed H5N1 virus before the onset of clinical signs (Brown et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have reported temporal and spatial overlap between global H5N1 outbreaks and bird migration patterns (e.g. Gilbert et al 2006;Si et al 2009) and some species held under laboratory conditions have been seen to shed these viruses without overt clinical symptoms (Keawcharoen et al 2008). Yet most isolations of HPAI viruses in wild birds are from dead or moribund individuals, with only three reported cases of HPAI H5N1 from apparently healthy birds (Feare 2010).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Viral transmission between migratory waterfowl and domestic bird populations, in either direction, can occur through several mechanisms, including direct contact in areas where the 2 groups share environments, scavenging on H5N1 HPAI virus-infected carcasses, and through ''bridge'' species that can transmit the virus between domestic poultry and migratory waterfowl populations. Small terrestrial birds commonly found around poultry environments have a strong potential to serve as important ''bridge'' species owing to their peridomestic behavior and extensive interaction with both free-living and domesticated avian populations.…”
Section: Introductionmentioning
confidence: 99%